Brexit : a moment of negation in the European passive revolution - Gülşen, Volkan (My University, 2022)
Bu tez, Brexit sürecinin temel dinamiklerini ve Avrupa Birliği sınıfsal yapısına etkisini Gramscici bir teorik çerceve içerisinde açıklamayı hedeflemektedir. Avrupa entegrasyon projesini, bir pasif devrim olarak, Brexit sürecini ise Avrupa Birliği sınıf tarihi içerisindeki bir olumsuzlanma momenti olarak kavramsallaştırmayı önermektedir. Buna göre, Birleşik Krallık’ın AB’den ayrılması daha şimdiden Avrupa sınıf yapısını değiştirmiş ve Avrupa pasif devriminin şu anki aşamasının gömülü neoliberal yapısını olumsuzlayarak dönüştürücü ekonomik ve politik dinamiklere katkı sağlamıştır. Yalnız, bu dinamikler çözülme itici faktörlerini tetiklemek yerine, neoliberal sosyal ve sınıf güçlerinin hegemonik geri çekilişi nedeniyle Avrupa Birliği kurumsal yapısında ulus-ötesi müdahaleciliğe dayanan yeni bir derinleşme başlatabilecektir.

This dissertation aims to explain the main dynamics of the Brexit process and its influence on the European Union class structure in a Gramscian theoretical framework. It suggests that the European integration process can be conceptualised as a passive revolution and the process of Brexit as a moment of negation in the European Union history of class struggle. It will be argued that the withdrawal of the United Kingdom has already altered the European class structure and contributed to the transformative economic and political dynamics which may negate the embedded neoliberal structure of the current stage of the European passive revolution. These dynamics would not seem to trigger the driving factors of the disintegration, but rather the hegemonic withdrawal of the neoliberal social and class forces may initiate a new deepening in the European Union institutional structure based on supranational interventionism.
Keywords: Avrupa Birleşik Devletleri; Avrupa Birliği; Avrupa Entegrasyonu ve Çözülmesi Brexit; Avrupa Pasif Devrimi; Brexit; corporate-liberalism; European Integration and Disintegration; European Passive Revolution; European Union; Fordism; Fordizm; Gramsci; Gramscian Civil Society; Gramscian Hegemony; Gramscici Hegemoni; Gramscici Sivil Toplum; International relations; korporatif-liberalizm; Pasif Devrim; Passive Revolution; Political science; Post-Fordism; Post-Fordizm; Post-Neoliberalism; Post-Neoliberalizm; Siyasal bilim; Thatcherism; Thatcherizm; Transnational Capitalist Class; Uluslararası ilişkiler; Ulusötesi Kapitalist Sınıf; United States of Europe